Perbaikan dan Akses Air Bersih di Mushola Nurul Huda Leweung Gede, Desa Tenjo, Kabupaten Bogor - Tommy Iduwin; Tri Yuhanah; Budi Wicaksono; Aryo Wibhowo (IKRA-ITH ABDIMAS, 2026)
The availability of adequate worship facilities and access to clean water constitutes a fundamental need that significantly influences the social and religious activities of local communities. The Mushola Nurul Huda, situated in the Leweung Gede Hamlet within Tenjo Village in Bogor Regency, has been grappling with constraints in its worship facilities and inadequate clean water infrastructure, which hinders the fulfillment of religious practices and the satisfaction of the daily needs of the congregation. This community service program sought to enhance the quality of worship facilities and improve access to clean water through a participatory approach involving local residents. The implementation stages comprised a needs assessment, technical planning, physical improvement of the mushola facilities, and the development and optimization of a clean water supply system adapted to local environmental conditions. The findings suggest a substantial enhancement in the functionality and comfort of the worship facilities, accompanied by enhanced reliability and sustainability in accessing clean water for the congregation. Beyond the tangible outcomes, the program fostered heightened community awareness and engagement in the maintenance and oversight of the enhanced facilities. On the whole, the initiative under consideration provides practical benefits in terms of supporting religious activities and improving the quality of life of the community surrounding Mushola Nurul Huda.